Changes in the policy environment for infant and young child feeding in Vietnam, Bangladesh, and Ethiopia, and the role of targeted advocacy - Harris, Jody; Frongillo, Edward A.; Nguyen, Phuong Hong; Kim, Sunny S.; Menon, Purnima (Springer, 2017)
There is limited literature examining shifts in policy environments for nutrition and infant and young child feeding (IYCF) over time, and on the potential contribution of targeted advocacy to improved policy environments in low- and middle-income countries. This study tracked changes in the policy environment over a four-year period in three countries, and examined the role of targeted nutrition and IYCF advocacy strategies by a global initiative. Qualitative methods, including key informant interviews, social network mapping, document and literature review, and event tracking, were used to gather data on nutrition and IYCF policies and programs, actor networks, and perceptions and salience of nutrition as an issue in 2010 and 2014 in Bangladesh, Ethiopia, and Vietnam. Theoretical frameworks from the policy sciences were used to analyze policy change over time, and drivers of change, across countries. The written policy environment improved to differing extents in each country. By 2014, the discourse in all three countries mirrored international priorities of stunting reduction and exclusive breastfeeding. Yet competing nutrition priorities such as acute malnutrition, food insecurity, and nutrition transitions remained in each context. Key actor groups in each country were government, civil society, development partners and the private sector. Infant formula companies, in particular, emerged as key players against enforcement of IYCF legislation. The role of a targeted IYCF advocacy and policy support initiative was well-recognized in supporting multiple facets of the policy environment in each country, ranging from alliances to legislation and implementation support. Despite progress, however, government commitment to funding, implementation, and enforcement is still emerging in each country, thus challenging the potential impact of new and improved policies. Targeted policy advocacy can catalyze change in national nutrition and IYCF policy environments, especially actor commitment, policy guidance, and legislation. Implementation constraints – financing, capacity and commitment of systems, and competing priorities and actors – are essential to address to sustain further progress. The lack of pressing political urgency for nutrition and IYCF, and the uncertain role of international networks in national policy spaces, has implications for the potential for change.